The Effect Of Combination Of Giving Decoction Of Salam And Ginger Leaves On Reduction Of Uric Acid Levels In The Elderly At Pondok Gede Health Center - Geger Nur Saputra; Desridius Chalid (Malahayati Nursing Journal, 2022)
ABSTRACT The elderly are at risk for health problems, namely Gout Arthritis, a joint disease caused by high levels of uric acid. Salam leaves and ginger are known as cooking spices, and can be an alternative medicine for cholesterol, diabetes mellitus, hypertension, gastritis, and gout. Objective to determine the effect of the combination of giving boiled bay leaves and ginger on reducing uric acid levels in the elderly at Pondok Gede Health Center in 2022. Research method analytical research with cross sectional approach. There were 30 elderly respondents with gout arthritis at Pondok Gede Health Center. The results of the study: Statistical test obtained P value of 0.001 0.05, Ha accepted Ho rejected. So there is a significant effect between giving bay leaves and ginger to reducing uric acid levels in the elderly at Pondok Gede Public Health Center in 2022. There is an Effect of Combination of Giving Decoction of Salam and Ginger Leaves on Reducing Uric Acid Levels in the Elderly at Pondok Gede Health Center in 2022 Keywords: Elderly, Salam and Ginger Leaves, Uric Acid. ABSTRAK Lansia beresiko dengan masalah kesehatan yaitu Gout Arthritis, penyakit sendi yang disebabkan oleh tingginya kadar asam urat. Daun Salam dan jahe dikenal sebagai bumbu masakan, dapat menjadi alternatif obat untuk kolesterol, diabetes mellitus, hipertensi, gastritis, dan asam urat. Tujuan penelitian untuk mengetahui pengaruh kombinasi pemberian rebusan daun salam dan jahe terhadap penurunan kadar asam urat pada lansia di Puskesmas Pondok Gede tahun 2022. Metode penelitian dengan pendekatan cross sectional. Responden lansia penderita gout arthritis di Puskesmas Pondok Gede, sebanyak 30. Hasil penelitian uji statistik didapatkan nilai P value 0,001 0,05, Ha diterima Ho ditolak. Maka ada pengaruh yang signifikan antara pemberian daun salam dan jahe terhadap penurunan kadar asam urat pada lansia di puskesmas pondok gede tahun 2022. Ada Pengaruh Kombinasi Pemberian Rebusan Daun Salam Dan Jahe Terhadap Penurunan Kadar Asam Urat Pada Lansia di Puskesmas Pondok Gede Tahun 2022. Kata kunci : Lansia, Daun Salam dan Jahe, Asam Urat.